MARIGINALISASI GENDER DALAM TEKS SATUA TANTING MAS DAN TANTING RAT - Ida Bagus Gede Paramita (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2022)
The purpose of this study is to examine the gender marjinalization in the texts of the satua Bali Tanting Mas and Tanting Rat. The aspect studied in this article is the relationship between text and context, the characters contained in the unit are seen as aspects of ideology, power and how things are in today's society. The method used in this research is qualitative method. Primary data was obtained from the text of the "satua" Tanting Mas and Tanting Rat, while secondary data was obtained from books and online publications that support the research discussion. The collected data is then selected to assist the analysis and the last step is drawing conclusions. The result of this research is the discovery of a culture that has been built that patriarchal ideology, women are marginalized figures, both those depicted in the texts of Tanting Mas and Tanting Rat as well as in their social reality.Keywords: Maginal, Gender and satua